2x+(x+3)=47

Simple and best practice solution for 2x+(x+3)=47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+(x+3)=47 equation:


Simplifying
2x + (x + 3) = 47

Reorder the terms:
2x + (3 + x) = 47

Remove parenthesis around (3 + x)
2x + 3 + x = 47

Reorder the terms:
3 + 2x + x = 47

Combine like terms: 2x + x = 3x
3 + 3x = 47

Solving
3 + 3x = 47

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 3x = 47 + -3

Combine like terms: 3 + -3 = 0
0 + 3x = 47 + -3
3x = 47 + -3

Combine like terms: 47 + -3 = 44
3x = 44

Divide each side by '3'.
x = 14.66666667

Simplifying
x = 14.66666667

See similar equations:

| 9x+2y+3z=0 | | 7x=8.2 | | 16x^2+28x+52=0 | | 16m=7m+72 | | -(2-x)-3(6+8x)-7x= | | 16x^2+28+52=0 | | 3(x+8)-2(x-6)=13 | | f(x)=x^2-4x-10 | | (8x^2-3x)-(6x^2-8x)= | | 5x+2-4x=7-10 | | 130+10x=3.5x | | y-160=-8(x-10) | | 22-m=116 | | 100=6y+y^2 | | x+2x+5x=2x+2x+8 | | 2x+10+x+2x-1=196 | | 7.8x-1.4=22.0 | | 2x+12x=3x-15 | | 3x+4+(1-4x)=1+x-27-2(x-16) | | -6(y+5)=-2y-42 | | 3w-30=9(w-8) | | (2x+8-3)(2x+8-3)= | | 9(x+5)=-9x-9 | | 10=-2v+4(v+6) | | (n+5)(n-3)=(n+1)(n-6) | | -36=-4w+6(w-4) | | 15=-16t^2+44t+5 | | 16=6y+7(y+6) | | X^2-2y^2-8y=0 | | 5(1+x^7)=20 | | 3x+4+(1-4x)=1+x-2(x-16) | | 3x-37.5=-3.41 |

Equations solver categories